Structure of the Temporal Rythme and its Implications in the Novel ''Fish do not Care'' by Inaam Beyud - CHETIOUI BOUDJEBIBA, Djowhara; ALATRACHE , Rabeh (Milev Journal of Research and Studies, 2020)
Abstract: This article aims analysing t the rhythmic mechanisms in the novel "Fish does not care" by " Inaam Beyud ", namely: mechanisms to accelerate it [Ellipse], the Sommaire, the frequency Le récit itératif, (Lerécit répetitif), and the mechanisms of its equilibrium [external dialogue (dialogues), internal dialogue (monologue)], how these mechanisms are employed, and how to reveal their expressive variations, For her.